Pengelolaan Sumber Daya Pesisir Tianyar Mengedepankan Pendekatan Nonkonfrontatif Berbasis Tri Hita Karana Mendukung One Map Policy Blue Economy Berkelanjutan - Ketut Sari Adnyani; Kadek Dedy Suryana; Ni Made Wiratini; Ni Putu Ega Parwati (Universitas Tabanan, 2026)
The purpose of this study focuses on the integration of coastal natural resource conservation policies with supporting components to strengthen the social institutions of the Yowana Bhakti Segara Foundation. Support from the village government, traditional villages, and the Tianyar community is directed at understanding the legal, social, economic, and cultural issues related to integrated coastal natural resource management. Research method: field research. Informants and respondents were determined purposively. Data collection techniques included document studies, observations, interviews, and questionnaires. SWOT analysis through FGD stages, Expert Testing, and Public Testing of the formulation and finalization of the policy. The results show that a non-confrontational approach based on Tri Hita Karana supports the One Map Policy for coastal management by harmonizing human relations with nature and God, creating social and ecological harmony through active participation (Pawongan), minimizing conflict, and integrating local wisdom (Parhyangan) into spatial regulations (Palemahan), resulting in sustainable, equitable, and sustainable coastal management, overcoming overlapping regulations and short-term economic interests that have been challenges.